TEST THE ANTIBACTERIAL ACTIVITY OF ETHANOL EXTRACT OF CRASSOCEPHALUM CREPIDIOIDES LEAF AGAINST STREPTOCOCCUS PYOGENES - anggraeni, Ratih; Lingga, Nola Monalisa (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2022)
The ethanol extract of Crassocephalum crepidioides leaves was tested against Streptococcus pyogenes bacteria. Extracts from the leaves of Crassocephalum crepidioides are known to have the potential to suppress microbial growth because contain active compounds of alkaloids and flavonoids. The test was carried out by the diffusion method using disc paper that had been soaked in a solution of ethanol extract of Crassocephalum crepidioides leaves with a concentration of 20%, 30%, 40%, 50%. Amoxicillin as a positive control and DMSO as a negative control. It is known that the inhibition of bacterial growth at a concentration of 20% the inhibition zone is 11mm, the concentration of the inhibition zone of 30% is 11.8mm, the concentration of 40% of the inhibition zone is 12.2mm, the concentration of 50% is the inhibition zone is 12.6mm. The higher the concentration of the ethanol extract of Crassocephalum crepidioides leaves, the wider the area of inhibition against Streptococcus pyogenes bacteria.